Mineral and trace element analysis of non-conventional food plants using ICP OES and chemometric techniques - da Silva Rodrigues, Leticia [UNESP]; Ferreira, Dennis Silva; Pereira-Filho, Edenir Rodrigues; Pereira, Fabiola Manhas Verbi [UNESP] (Elsevier, 2025)
Non-conventional food plants (or non-conventional edible plants) have the potential to serve as an excellent nutritional alternative while promoting the circular economy. Given the nutritional potential of non-conventional food plants, this study aimed to investigate and determine the composition of these plants using inductively coupled plasma optical emission spectroscopy (ICP OES) combined with chemometric techniques. In this context, the following non-conventional food plant species were evaluated: serralha (Sonchus oleraceus), two species of ora-pro-nóbis, Pereskia grandifolia and Pereskia aculeata, peixinho (Nematanthus gregarius), alfavaca (Ocimum basilicum), taioba (Xanthosoma sagittifolium), capeba (Pothomorphe umbellata), tranchagem (Plantago major), and bardana (Arctium lappa). Ten elements (Ca, K, Mg, P, S, Cu, Fe, Mn, Sr, and Zn) were determined with concentrations varying from 4.62 (Cu) mg kg-1 up to 0.15 (P) g 100 g-1. Statistical tests (one-way ANOVA) were applied as long as principal component analysis (PCA) and no differences between non-conventional and conventional food plants were verified.